24 Should fractional flow reserve follow angiographic visual inspection to guide preventive PCI in STEMI?. (17th July 2020) - Hadyanto, Steven; Wald, David; Bestwick, Jon
Abstract : Introduction: Evidence of the benefit of preventive percutaneous coronary intervention (PCI to non-infarct arteries) in patients with ST-elevation myocardial infarction (STEMI) has increased with the publication of several randomised trials, but marked variation in the magnitude of benefit on hard outcomes has been observed between trials. One possible explanation for the difference in results is the way non-infarct artery stenoses are selected for preventive PCI. We aimed to quantify the effect of preventive PCI on cardiac death and non-fatal myocardial infarction (MI) according to whether the decision to carry out preventive PCI was based on angiographic visual inspection (AVI alone) or AVI plus Fractional Flow Reserve if AVI showed significant stenosis (AVI plus FFR). Methods: Randomised trials comparing preventive PCI with no preventive PCI in STEMI without shock were identified by a systematic literature search and categorised according to whether they used AVI alone or AVI plus FFR to select patients for preventive PCI. Trials that used both methods without reporting results separately were excluded. Random effects meta-analyses and tests of heterogeneity were used to compare the two categories in respect of cardiac death and MI, as the primary outcomes, individually and together. All-cause death was considered as a secondary outcome. Results: Eleven eligible trials were identified including 3150 patients, median age 62 years and 78% male with follow-up ranging between 6 months and 3 years. The results of the primary comparative analyses are shown in the Figure 1 . For cardiac death the relative risk estimates for AVI alone versus AVI plus FFR were 0.38 (0.20-0.73) and 0.79 (0.36-1.77) respectively (p=0.15 for difference), for MI 0.41 (0.23-0.73) and 1.23 (0.79-1.92) respectively (p=0.02 for difference) and for cardiac death and MI 0.41 (0.26-0.63) and 0.85 (0.57-1.28) respectively (p=0.01). Figure 2 gives the result for all-cause death. One large trial (COMPLETE) could not be included because it mixed both methods; the result (relative risk 0.74 for cardiac death and MI) was in between the effect using AVI alone and AVI plus FFR respectively. Conclusions: In preventive PCI among STEMI patients, AVI alone achieves an approximate 60% reduction in cardiac death and MI but selecting patients using FFR in AVI positive patients loses much of the benefit. AVI is best used without FFR in this group of patients. Conflict of Interest: None